Kompetensi Profesional Guru Sanggar Gambar Anak Usia Dini (4-6 TAHUN) - Prayitno (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2023)
The professional competence of drawing studio teachers is an important part of the quality of management of non-formal education institutions, the scope of early childhood education (PAUD). Professional competence is something that every teacher who teaches in studios or drawing courses must have. This research is based on questions from parents regarding the professional competence of studio teachers, some have a bachelor's background in fine arts education, some have a non- educational fine arts background, there are also those who don't have a graduate background but can draw or are known to be autodidacts, there are even some educational background other than fine arts but can draw, and so on. This research aims to describe one of the teacher competencies, namely the professional competency of studio teachers in the city of Bandung. The method in this research is qualitative with a descriptive analysis approach. Data collection in this research used observation techniques, interviews, and students' drawings. The subjects of this research were three studio teachers from different locations in Bandung City. This research shows that of the three drawing studio teachers, there are two teachers who have good professional competence, while one teacher has professional competence in the quite good category. An institution or drawing studio that has good professional teacher competence will influence the quality, so that parents will have more confidence in the studio. It is hoped that this article can become a reference and knowledge for prospective educators regarding the professional competence of drawing studio teachers.